Study of the effect of some manufacturing and operating defects on the unbalance of rotating shafts using MATLAB - السلومي, أنس; موفق المنجد (Latakia University Journal -Engineering Sciences Series, 2024)
Rotary machines are widely used in mechanical and electromechanical systems that include motor axes, industrial turbine turbines, etc., in the case of an unbalanced distribution of the rotating masses around the axis of rotation, which leads to vibrations, which is a serious engineering problem that negatively affects the performance of these machines, where vibration occurs In any rotating machine due to manufacturing or operational defects, etc., these harmful vibrations are accompanied by the emergence of large centrifugal forces that can lead to damage to the bearings and eventually to the destruction of the machines. Therefore, vibration reduction techniques in such machines are of prime importance to improve performance . One of the techniques used to improve the work of the rotary shaft is the shaft balancing technique, which is based on reducing vibration to a minimum (as practically vibrations cannot reach zero values), thus increasing the life of the bearings, reducing audible noise and energy loss, and thus improving the work of the rotor. The aim of modeling and simulation of rotor systems is to study and determine the deflection of the rotating body due to vibration and to calculate the position and additional masses needed to remove the vibration when rotating at high speeds. In this research, we designed a mathematical model used to study the static behavior of rotating axes and to determine deviations at high speeds using MATLAB/SIMULINK software..